Preliminary design of double rubber belt continuosly variable transmission (CVT) - Mohd Fadzli, Mansor (2009)
A vehicle that is powered by an internal combustion engine (ICE) needs a transmission system to change the transmission ratio between the engine and the drive wheel for smooth and comfortable drive. Rubber belt continuous variable transmission (CVT) is commonly used in scooter with small engine. The engine with capacity above 200 cc need more torque to deliver its power; hence it needs modification at its CVT to overcome this problem. Research and development in continuous variable transmission (CVT) for scooter show variety of possibility. One of them is by modifying single rubber belt CVT into double rubber belt. The objective of this work is to study the preliminary requirement for designing double rubber belt CVT. This paper introduces an alternative way of changing CVT ratio for double rubber belt system using mechanical system. This new system introduces a Tshape housing for the ball roller as a mechanism of shifting the pulley ratio. The ball roller regulated the axial movement of two movable pulley sheave to shift the two rubber belt place between the sheaves, and change the belt-pulley contact radius. Changing this contact radius means changing the CVT ratio. To support the design requirement some calculation was made and CAE software was used to analyze force distribution on input shaft. From the analysis, it shows that the shaft still can support with two rubber belt system to generate the power in high revolution. The result shows that the new system using two rubber belt system and application of the ball rollers in T-shape housing gives more torque to deliver of power machine and this system approach that can be used as the new technology for automotives industry.